Synthetic post-translational protein modification as a switch for activity - Faulkner, SC (2019)
The ‘post-translational mutagenesis’ chemistry, utilising a bio-orthogonal radical reaction with Dha on proteins, has opened up a vast range of novel possibilities in generating post- translational modification (PTM) mimics. Two case studies are described in this thesis, around the theme of PTMs as switches for protein-protein interactions. The first case study recapitulates the natural PTMs H3K36me2 and -me3. Functional evidence from in vivo observations suggests that the chromodomain reader protein MRG15 should preferentially bind H3K36me3 over its dimethyl counterpart. However, in vitro studies using peptides or isolated H3 as a substrate have failed to recapitulate this observation. Here, using synthetic, ‘post-translational mutagenesis’, fully-intact model nucleosomes containing both H3K36me2 and H3K36me3 were generated. Binding of MRG15 to these intact nucleosomes revealed a marked preference for H3K36me3 containing nucleosomes over those containing H3K36me2, recapitulating physiologically relevant observations. A model was suggested in which the H3K36 side chain is normally sequestered in intact nucleosomes in a hydrogen bonding interaction with the phosphate of the DNA backbone, and the interaction entirely abrogated only when the third methyl group is added to form H3K36me3, providing a ‘methyl- switch’ mechanism for context-dependent reader selectivity. The second case study was centred around installing a natural PTM in an unnatural location to produce a novel sensor. Dha chemistry was once again employed to install O- and N-linked GlcNAc mimics in the complement determining region (CDR) of a nanobody cAbLys3, with the aim of reversibly blocking its antigen binding capacity. Enzymatic extension of cAbLys3- O-GlcNAc to produce an Fc decasaccharide was also investigated as an alternative means of tuning a nanobody’s effects for potential therapeutic applications. Overall, the aim of this thesis was to demonstrate the use of the post-translational mutagenesis method to install mimics of labile PTMs; both to study their function in a natural setting, and to create novel biosensors.